The role of Neuropilin-1 as a SARS-CoV-2-specific endocytosis potentiator - Yamauchi, Yohei (Henry Stewart Talks, 2021)
Differences in the structure and biological properties of SARS-CoV-2 Spike proteins compared to those of other coronaviruses (including SARS), The distinct profile of the distribution of SARS-CoV-2-infected cells, particularly in lung and epithelial tissue, compared to other coronaviruses, SARS-CoV-2’s Spike protein sequence grants it the unique ability to interact with Neuropilin-1, in addition to ACE2, Role of Neuropilin-1, a cell-surface co-receptor, in facilitating mechanisms of SARS-CoV-2 entry into cells, Current understanding of the influence of Neuropilin-1 on the development of COVID-19 and on disease progression, The potential of developing SARS-CoV-2-specific antiviral drugs targeting Neuropilin-1.